Peran Guru PKn Dalam Pembentukan Sikap Sopan Santun Siswa Kelas III SDN Banyuajuh 04 Bangkalan (Adi Widya: Jurnal Pendidikan Dasar, 2023)
Based on the research findings regarding the form of cultivating polite characters in class III students at Elementary School of Banyuajuh 4, it was found that the cultivation of polite characters includes three main aspects, namely politeness in appearance, politeness in communicating, and politeness in behavior. In this case, students are given an understanding of the consequences of impolite behavior, as well as the importance of being polite in creating a harmonious environment. The subjects in this study included class teachers and class III students at Elementary School of Banyuajuh 4 Bangkalan. This research uses qualitative research methods by collecting data through documentation observation sheets. The technique of analyzing data is using data reduction techniques, data display, and conclusions (data verification). With this observation, it can be concluded that students at Elementary School of Banyuajuh 4 have formed attitudes and polite behavior in interactions with teacher.